CSR, Gender Diversity, and Firm Performance: Evidence from Mining and Energy Sector In Indonesia - Goiyardi, David; Joni, Joni (Universitas Kristen Maranatha, 2025)
Purpose – This study aims to examine the relationship between Corporate Social Responsibility (CSR) and Gender Diversity on Firm Performance in the mining and energy sector in Indonesia. Design/methodology/approach – This study used purposive sampling with listed energy and mining companies in Indonesia as the main criteria. The final sample is 444 firm-year observation. In this study, OLS regression was used to test this relationship. This study also resolved the endogeneity issue by employing the Generalized Method of Moments (GMM). Findings – The analytical results reveal that there is a positive relationship between CSR and Gender Diversity and firm performance. Companies that employ strong CSR initiatives tend to fare better. Furthermore, the findings indicate that gender diversity has a positive impact on firm performance. Research limitations/implications – This study has important implications for stakeholders and firms in the mining and energy industries in Indonesia. Strong CSR practices and the promotion of gender diversity can give long-term benefits for businesses, such as increased reputation, employee satisfaction, and the production of new value for shareholders. These findings can also be used by the government and relevant organizations to design laws and regulations that encourage sustainable and equitable business practices in Indonesia's mining and energy sectors. Keywords: CSR, Gender Diversity, Firm Performance, Energy and Mining Sector